2018
DOI: 10.1002/eat.22984
|View full text |Cite
|
Sign up to set email alerts
|

The QTc interval and risk of cardiac events in bulimia nervosa: A long‐term follow‐up study

Abstract: Objective An association between bulimia nervosa (BN) and prolonged corrected QT interval (QTc) in the electrocardiogram has been suggested, but results of previous studies are conflicting, and the risk of cardiac events in patients with BN has yet to be investigated. Method We estimated mean QTc interval and relative risk of borderline (QTc >440 ms) and prolonged QTc (QTc >460 ms) between adult women with BN (N = 531) and healthy controls (N = 123). In follow‐up analyses, we investigated the risk of a primary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 33 publications
(50 reference statements)
0
8
0
Order By: Relevance
“…1 Electrical conduction defects in bulimia coincide with electrolyte imbalance and hypokalemia. [19][20][21] In women diagnosed with severe bulimia and hypokalemia, QT interval prolongation and repolarization abnormalities may lead to sudden acute ventricular arrhythmias and death. 21 A study of 52 women diagnosed with bulimia in the United States who binged and purged found a lower R-wave amplitude on the electrocardiogram, indicating reduced cardiac contractile force and signaling.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…1 Electrical conduction defects in bulimia coincide with electrolyte imbalance and hypokalemia. [19][20][21] In women diagnosed with severe bulimia and hypokalemia, QT interval prolongation and repolarization abnormalities may lead to sudden acute ventricular arrhythmias and death. 21 A study of 52 women diagnosed with bulimia in the United States who binged and purged found a lower R-wave amplitude on the electrocardiogram, indicating reduced cardiac contractile force and signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the literature focuses on acute consequences, including immediate hemodynamic changes and electrical conduction defects due to excessive purging and fluid loss. [19][20][21] Bulimia is associated with reduced blood pressure, pulse rate, and oxygen saturation during active disease. 1 Electrical conduction defects in bulimia coincide with electrolyte imbalance and hypokalemia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, a large register‐based study found that the risk of ventricular tachycardia and syncope is increased in patients with AN compared with the background population (Frederiksen, Krogh Christiansen, et al., 2018), which is in line with the previous theory that an increased risk of QTc prolongation on the ECG, and subsequently polymorphic ventricular tachycardia, could partly explain the increased cardiovascular death in patients with AN (Sachs et al., 2016). However, the three largest studies on the matter found no increased risk of QTc prolongation in patients with AN or BN (Frederiksen, Christiansen, et al., 2018; Frederiksen, Krogh Christiansen, et al., 2018; Krantz et al., 2020). Therefore, the background for the increased risk of cardiovascular death in these patients is still unresolved.…”
Section: Introductionmentioning
confidence: 99%